Smooth discrimination analysis - Enno Mammen; Aleksandr B. Tsybakov (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Discriminant analysis for two data sets in IRd with probability densities f and g can be based on the estimation of the set G = x : f(x) Ï g(x). We consider applications where it is appropriate to assume that the region G has a smooth boundary. In particular, this assumption makes sense if discriminant analysis is used as a data analytic tool. We discuss optimal rates for estimation of G.
urn:nbn:de:kobv:11-10056389
Keywords: 330; minimax rates; discrimination analysis; Bayes risk